Vitamin D(3)-dependent VDR signaling delays ron-mediated breast tumorigenesis through suppression of β-catenin activity - Johnson, Abby L. (Oncotarget, 2015)
The Ron receptor is upregulated in human breast cancers and correlates with enhanced metastasis and reduced patient survival. Ron overexpression drives mammary tumorigenesis through direct β-catenin activation and augmented tumor cell proliferation, migration and invasion. Ron and β-catenin are also coordinately elevated in breast cancers. The vitamin D receptor (VDR) antagonizes β-catenin signaling. Herein, we examined mammary tumor onset and progression using a Ron-driven murine model of breast tumorigenesis crossed with VDR deficient mice. VDR ablation accelerated mammary tumor onset and led to tumors that exhibited a desmoplastic phenotype and enhanced metastases. Tumor levels of active β-catenin were markedly increased in the absence of VDR. In vitro, VDR activation in breast cancer cells reduced β-catenin activation and transcriptional activity leading to elevated expression of the extracellular Wnt inhibitor dickkopf-related protein 1, and a reduction in the interaction of β-catenin with the cyclin D1 promoter. Expression of a stabilized form or β-catenin ablated the protective effects of VDR activation. Collectively, these studies delineate a protective role for VDR signaling in Ron-induced mammary tumorigenesis through disruption of β-catenin activation.